Remarks on the genus Tamdaotettix Gorochov, 1998 (Orthoptera: Rhaphidophoridae: Aemodogryllinae) from China - Zhu, Qidi; Bian, Xun; Shi, Fuming (Zootaxa, 2018)
In this paper, a new species of the genus Tamdaotettix from China, Tamdaotettix (Tamdaotettix) longituberus sp. nov., is described, with a new recorded species, Tamdaotettix (Tamdaotettix) dilutus Gorochov, 1998 from China. The morphological photographs of Tamdaotettix (Tamdaotettix) longituberus sp. nov., Tamdaotettix (Tamdaotettix) dilutus Gorochov, 1998, Tamdaotettix (Tamdaotettix) tridenticulatus Qin, Liu & Li, 2016 and the distribution data of the genus Tamdaotettix from China are provided. All specimens examined are preserved in the Museum of Hebei University.